Evaluating an oral health programme for the prevention of dental decay among school-aged children in China: protocol for a mixed-methods study based on the RE-AIM framework. Issue 9 (30th September 2022) - Wang, Lidan; Liu, Hueiming; Wang, Li; Zhang, Yanqun; Guo, Wei; Wu, Peilin; Chang, Xiangxiang; Wang, Li; Xu, Wenhua; Zhao, Linhai
Abstract : Introduction: The objective of the Comprehensive Intervention of Oral Disease for Children (CIODC) in China is to prevent dental decay for school-aged children and provide free prevention services in pilot areas beginning in 2008. It is a potentially affordable, acceptable and effective prevention strategy to use for more school-aged children in the future. There is a shortage of robust evidence regarding the cost-effectiveness, feasibility and scalability of prevention strategies for dental decay for school-aged children in China. This study aims to provide a comprehensive evaluation, including an economic evaluation and process evaluation, to better understand how and why the public health programme may be effective and economical. Methods and analysis: Mixed methods will be used in this study. Cost-effectiveness analysis (CEA) will be conducted from a societal perspective, based on a modelling study over 6 years (from age 7 to 12) in terms of the incremental cost-effectiveness ratios per dental decay averted. The Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework informed the process evaluation. An estimated 48–80 semistructured interviews with service providers, patient parents/caregivers and decision-makers under the logic model will be used in the progress evaluation to describe the feasibility and sustainability of CIODC. Ethics and dissemination: The study has all necessary ethical approvals from the Ethics Committee of Anhui Medical University (number 2021H030). All participants will provide informed consent prior to participation. Findings will be disseminated through conference presentations and scientific publications in peer-reviewed journals.